2016
DOI: 10.1016/j.jaac.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Male Eating Disorder Symptom Patterns and Health Correlates From 13 to 26 Years of Age

Abstract: Objective-Research on the manifestations and health correlates of eating disorder symptoms among males is lacking. This study identified patterns of appearance concerns and eating disorder behaviors from adolescence through young adulthood and their health correlates.Method-Participants were 7,067 males from the prospective Growing Up Today Study. Surveys from 1999-2007 (spanning ages 13-26 years) provided repeated measures data on: muscularity and leanness concerns; eating disorder behaviors (purging, overeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 41 publications
(42 reference statements)
3
44
0
Order By: Relevance
“…Our longitudinal findings confirm previous literature finding associations between muscularity‐oriented disordered eating and substance use (Calzo et al, ) and depression (Grossbard et al, ; Olivardia et al, ). Overall, poor adolescent mental health and well‐being as well as substance use may predict future engagement in muscularity‐oriented disordered eating behaviors in young adulthood.…”
Section: Discussionsupporting
confidence: 91%
“…Our longitudinal findings confirm previous literature finding associations between muscularity‐oriented disordered eating and substance use (Calzo et al, ) and depression (Grossbard et al, ; Olivardia et al, ). Overall, poor adolescent mental health and well‐being as well as substance use may predict future engagement in muscularity‐oriented disordered eating behaviors in young adulthood.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have similarly showed that body dissatisfaction in males is associated with depression Calzo et al, 2016;Holsen, Kraft, & Roysamb, 2001;Paxton, Eisenberg, & Neumark-Sztainer, 2006). Previous studies have similarly showed that body dissatisfaction in males is associated with depression Calzo et al, 2016;Holsen, Kraft, & Roysamb, 2001;Paxton, Eisenberg, & Neumark-Sztainer, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…Important limitations to highlight, however, relate to attrition, which was relatively high at age 18, and was higher amongst girls who were assigned to symptomatic classes vs. those in the asymptomatic class at 14 years of age; low power to investigate boys, due to low endorsement of ED symptoms under study. This might be due to the questions included as indicators, maybe geared towards female-specific ED behaviours and cognitions[38,39]. Indicators used were based on questions derived from the Youth Risk Behavior Surveillance System questionnaire[22], therefore symptoms were self-reported and fewer behaviours consistent with anorexia nervosa were present in the questionnaire, therefore limiting our ability to investigate anorexia-type behaviours.…”
Section: Discussionmentioning
confidence: 99%